Optical laminate, lens unit, and display method
The optical laminate addresses the weight and visibility issues in VR goggles by integrating a lightweight laminate film with a retardation member and adhesive layers, enhancing image clarity and durability.
Patent Information
- Application Number
- JP2024190255
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-28
AI Technical Summary
Existing VR goggles are heavy and hinder visibility due to thick lenses, necessitating the development of lightweight optical members for improved image display systems.
An optical laminate comprising a laminate film with a base material and surface treatment layer, incorporating a retardation member with specific thickness and refractive index characteristics, and adhesive layers to enhance smoothness and durability, integrated into a lens unit for VR goggles.
The optical laminate reduces the weight of VR goggles while improving visibility by minimizing light leakage and ensuring clear image transmission.
Smart Images

Figure 2025013376000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate, a lens portion, and a display method. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as polarizing members and phase difference members are generally used to realize image display and to improve the performance of the image display (see, for example, Patent Document 1).
[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing virtual reality (VR) have begun to be commercialized. Since the use of VR goggles in various situations is being considered, there is a demand for them to be lightweight and have improved visibility. Weight reduction can be achieved, for example, by thinning the lenses used in the VR goggles. On the other hand, there is also a demand for the development of optical members suitable for display systems using thin lenses. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above, a primary object of the present invention is to provide an optical laminate that can reduce the weight of VR goggles and improve visibility. [Means for solving the problem]
[0006] 1. The optical laminate according to an embodiment of the present invention includes a laminated film having a base material and a surface treatment layer, and a retardation member. The base material of the laminated film and the retardation member are arranged adjacent to each other. The retardation member includes a first retardation layer, an adhesive layer, and a second retardation layer in this order, and the thickness of the adhesive layer is 0.5 μm or more and 1.3 μm or less. 2. The optical laminate according to 1 above may have a laminate smoothness of 0.7 arcmin or less. 3. In the optical laminate according to 1 or 2 above, the adhesive layer may be a cured layer of a resin. 4. In the optical laminate according to any one of 1 to 3 above, the surface smoothness of the laminated film may be 0.5 arcmin or less. 5. In the optical laminate according to any one of 1 to 4 above, the base material of the laminated film may contain a (meth)acrylic resin. 6. In the optical laminate according to any one of 1 to 5 above, the surface treatment layer of the laminated film may have an anti-reflection function. 7. In the optical laminate according to any one of 1 to 6 above, the first retardation layer may exhibit a refractive index characteristic of nx > ny ≧ nz and may satisfy the relationship of Re(450) < Re(550) < Re(650). 8. In the optical laminate according to any one of 1 to 7 above, the second retardation layer may exhibit a refractive index characteristic of nz > nx ≧ ny. 9. The optical laminate according to any one of 1 to 8 above may have a Y value of the visual sensitivity correction single transmittance of 93% or more. 10. A lens unit according to an embodiment of the present invention is a lens unit used in a display system that displays an image to a user, and comprises a reflective polarizing element that reflects light that is emitted forward from a display surface of a display element that displays an image and passes through a polarizing element and a first λ / 4 element, a first lens unit that is arranged on the optical path between the display element and the reflective polarizing element, a half mirror that is arranged between the display element and the first lens unit, transmits the light emitted from the display element and reflects the light reflected by the reflective polarizing element toward the reflective polarizing element, a second lens unit that is arranged in front of the reflective polarizing element, and an optical laminate described in any one of 1 to 9 above that is arranged on the optical path between the half mirror and the reflective polarizing element. 11. A display method according to an embodiment of the present invention includes the steps of passing light representing an image emitted through a polarizing element and a first λ / 4 element through a half mirror and a first lens unit, passing the light that has passed through the half mirror and the first lens unit through an optical laminate described in any one of 1 to 9 above, reflecting the light that has passed through the optical laminate toward the half mirror with a reflective polarizing element, making the light reflected by the reflective polarizing element and the half mirror transmittance through the reflective polarizing element using the optical laminate, and passing the light that has transmitted through the reflective polarizing element through a second lens unit. Effect of the Invention
[0007] According to the optical laminate according to the embodiment of the present invention, it is possible to realize a reduction in weight of VR goggles and an improvement in visibility. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing a general configuration of a display system according to an embodiment of the present invention. [Diagram 2] 2 is a schematic cross-sectional view showing an example of details of a lens portion of the display system shown in FIG. 1. [Diagram 3] FIG. 2 is a schematic perspective view showing an example of a multilayer structure included in a reflective polarizing film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0011] FIG. 1 is a schematic diagram showing a schematic configuration of a display system according to one embodiment of the present invention. In FIG. 1, the arrangement and shape of each component of a display system 2 are illustrated. The display system 2 includes a display element 12, a reflective polarizing member 14, a first lens unit 16, a half mirror 18, a first phase difference member 20, a second phase difference member 22, and a second lens unit 24. The reflective polarizing member 14 is disposed in front of the display surface 12a side of the display element 12, and can reflect light emitted from the display element 12. The first lens unit 16 is disposed on the optical path between the display element 12 and the reflective polarizing member 14, and the half mirror 18 is disposed between the display element 12 and the first lens unit 16. The first phase difference member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second phase difference member 22 is disposed on the optical path between the half mirror 18 and the reflective polarizing member 14.
[0012] The half mirror, or the components arranged forward from the first lens portion (in the illustrated example, the half mirror 18, the first lens portion 16, the second phase difference member 22, the reflective polarizing member 14, and the second lens portion 24) may be collectively referred to as the lens portion (lens portion 4).
[0013] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member (typically, a polarizing film) that may be included in the display element 12, and is converted into a first linearly polarized light.
[0014] The first phase difference member 20 includes a first λ / 4 member that can convert a first linearly polarized light incident on the first phase difference member 20 into a first circularly polarized light. When the first phase difference member does not include a member other than the first λ / 4 member, the first phase difference member may correspond to the first λ / 4 member. The first phase difference member 20 may be provided integrally with the display element 12.
[0015] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflective polarizing member 14 toward the reflective polarizing member 14. The half mirror 18 is provided integrally with the first lens portion 16.
[0016] The second phase difference member 22 includes a second λ / 4 member that can transmit light reflected by the reflective polarizing member 14 and the half mirror 18 through the reflective polarizing member 14. When the second phase difference member does not include any member other than the second λ / 4 member, the second phase difference member may correspond to the second λ / 4 member. The second phase difference member 22 may be provided integrally with the first lens portion 16.
[0017] The first circularly polarized light output from the first λ / 4 member included in the first phase difference member 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member included in the second phase difference member 22. The second linearly polarized light output from the second λ / 4 member is reflected toward the half mirror 18 without passing through the reflective polarizing member 14. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarizing member 14 is the same as the reflection axis of the reflective polarizing member 14. Therefore, the second linearly polarized light incident on the reflective polarizing member 14 is reflected by the reflective polarizing member 14.
[0018] The second linearly polarized light reflected by the reflective polarizing member 14 is converted into the second circularly polarized light by the second λ / 4 member included in the second phase difference member 22, and the second circularly polarized light output from the second λ / 4 member passes through the first lens unit 16 and is reflected by the half mirror 18. The second circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member included in the second phase difference member 22. The third linearly polarized light passes through the reflective polarizing member 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member 14 is the same as the transmission axis of the reflective polarizing member 14. Therefore, the third linearly polarized light incident on the reflective polarizing member 14 passes through the reflective polarizing member 14.
[0019] The light that has passed through the reflective polarizing member 14 passes through the second lens unit 24 and enters the user's eye 26.
[0020] For example, the absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member 14 may be arranged substantially parallel to each other or substantially perpendicular to each other. The angle formed by the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first λ / 4 member included in the first retardation member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle formed by the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second λ / 4 member included in the second retardation member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.
[0021] The in-plane retardation Re(550) of the first λ / 4 member is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm. The first λ / 4 member preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The first λ / 4 member preferably satisfies the relationship of Re(450) < Re(550) < Re(650). Re(450) / Re(550) of the first λ / 4 member is, for example, 0.75 or more and less than 1, and may be 0.8 or more and 0.95 or less.
[0022] The in-plane retardation Re(550) of the second λ / 4 member is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm. The second λ / 4 member preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The second λ / 4 member preferably satisfies the relationship of Re(450) < Re(550) < Re(650). Re(450) / Re(550) of the second λ / 4 member is, for example, 0.75 or more and less than 1, and may be 0.8 or more and 0.95 or less.
[0023] In the lens portion 4, a space may be formed between the first lens portion 16 and the second lens portion 24. In this case, it is preferable that the member disposed between the first lens portion 16 and the second lens portion 24 is integrally provided with either the first lens portion 16 or the second lens portion 24. For example, it is preferable that the member disposed between the first lens portion 16 and the second lens portion 24 is integrated with either the first lens portion 16 or the second lens portion 24 via an adhesive layer. According to such a form, for example, the handling of each member may be excellent. The adhesive layer may be formed of an adhesive or a pressure-sensitive adhesive. Specifically, the adhesive layer may be an adhesive layer or a pressure-sensitive adhesive layer. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm.
[0024] FIG. 2 is a schematic cross-sectional view showing an example of the details of the lens unit of the display system shown in FIG. 1. Specifically, FIG. 2 shows a first lens unit, a second lens unit, and a member disposed between them. The lens unit 4 includes a first lens unit 16, a first laminate unit 100 provided adjacent to the first lens unit 16, a second lens unit 24, and a second laminate unit 200 provided adjacent to the second lens unit 24. In the example shown in FIG. 2, the first laminate unit 100 and the second laminate unit 200 are disposed apart from each other. Although not shown, a half mirror may be provided integrally with the first lens unit 16. Hereinafter, the first laminate unit may be referred to as an optical laminate.
[0025] The first laminated unit 100 includes a second phase difference member 22 and an adhesive layer (e.g., a pressure-sensitive adhesive layer) 41 disposed between the first lens unit 16 and the second phase difference member 22, and is integrally provided with the first lens unit 16 by the adhesive layer 41. The first laminated unit 100 further includes a first protective member 31 disposed in front of the second phase difference member 22. The first protective member 31 is laminated on the second phase difference member 22 via an adhesive layer (e.g., a pressure-sensitive adhesive layer) 42, and disposed adjacent to the second phase difference member 22. The first protective member 31 may be located on the outermost surface of the first laminated unit 100. In this specification, "adjacent" includes not only "directly adjacent" but also "adjacent via an adhesive layer."
[0026] In the example shown in FIG. 2, the second retardation member 22 includes, in addition to the second λ / 4 member (first retardation layer) 22a, a member (second retardation layer) 22b having a refractive index characteristic showing the relationship of nz > nx ≧ ny. The second retardation member 22 has a laminated structure of the first retardation layer 22a and the second retardation layer 22b. By using the member 22b showing the relationship of nz > nx ≧ ny, light leakage (for example, light leakage in an oblique direction) can be prevented. As shown in FIG. 2, in the second retardation member 22, it is preferable that the second λ / 4 member 22a is positioned more forward than the member 22b showing the relationship of nz > nx ≧ ny.
[0027] The second λ / 4 member (first retardation layer) 22a and the member (second retardation layer) 22b showing the relationship of nz > nx ≧ ny are laminated via an adhesive layer 50. The second retardation member 22 includes the first retardation layer 22a, the adhesive layer 50, and the second retardation layer 22b. By laminating the retardation layers using the adhesive layer 50, the occurrence of cracks and fractures in the retardation layers can be suppressed. Also, peeling between the retardation layers can be prevented. And an optical laminate excellent in durability can be obtained. For example, when the thickness of at least one of the first retardation layer and the second retardation layer (for example, the second retardation layer) is 10 μm or less, cracks and fractures tend to occur easily.
[0028] The above second λ / 4 member preferably has a refractive index characteristic showing the relationship of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range not impairing the effects of the present invention, ny < nz may occur. The Nz coefficient of the second λ / 4 member is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0029] The second λ / 4 member is formed of any suitable material that can satisfy the above characteristics. The second λ / 4 member can be, for example, a stretched film of a resin film or an alignment solidified layer of a liquid crystal compound.
[0030] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination. Examples of methods for combining include blending and copolymerization. When the second λ / 4 member exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) may be suitably used.
[0031] Any suitable polycarbonate-based resin can be used as the polycarbonate-based resin. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diol, alicyclic dimethanol, di-, tri- or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for the second λ / 4 member and methods for forming the second λ / 4 member are described, for example, in JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.
[0032] The thickness of the second λ / 4 member made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, and more preferably 20 μm to 60 μm.
[0033] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. In the second λ / 4 member, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the second λ / 4 member (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.
[0034] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.
[0035] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0036] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.
[0037] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.
[0038] The thickness of the second λ / 4 member constituted by the liquid crystal alignment solidified layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and further preferably 1 μm to 4 μm.
[0039] The thickness direction retardation Rth(550) of the member (second retardation layer) whose refractive index characteristic shows the relationship of nz>nx≧ny is preferably −260 nm to −10 nm, more preferably −230 nm to −15 nm, and further preferably −215 nm to −20 nm. In one embodiment, the second retardation layer is a so-called positive C plate whose refractive index shows the relationship of nx=ny. Here, “nx=ny” includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. For example, it also includes the case where Re(550) is less than 10 nm. In another embodiment, the refractive index of the second retardation layer shows the relationship of nx>ny. In this case, the in-plane retardation Re(550) of the second retardation layer is preferably 10 nm to 150 nm, and more preferably 10 nm to 80 nm.
[0040] The member having the refractive index characteristic of nz>nx≧ny may be formed of any appropriate material. It is preferably composed of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of such liquid crystal compounds and methods for forming the film include the liquid crystal compounds and forming methods described in
[0020] to
[0042] of JP-A-2002-333642. In this case, the thickness is preferably 0.1 μm to 5 μm, more preferably 0.5 μm to 4 μm.
[0041] As another preferred example, the member having refractive index characteristics of nz>nx≧ny may be a retardation film made of a fumaric acid diester resin described in JP 2012-32784 A. In this case, the thickness is preferably 5 μm to 50 μm, and more preferably 10 μm to 35 μm.
[0042] The adhesive layer 50 included in the second phase difference member 22 may be formed of any appropriate adhesive. For example, the adhesive irreversibly changes from a liquid to a solid state during the process of forming the adhesive layer, has fluidity when applied, and has the property of being cured by a curing process (for example, irradiation with active energy rays, heating). As the adhesive, a curable adhesive is preferably used. Specifically, the adhesive layer 50 is preferably a cured layer of resin. As the curable adhesive, an ultraviolet-curable adhesive is preferably used.
[0043] The ultraviolet-curable adhesive contains a curable monomer such as a compound having a (meth)acryloyl group or a compound having a vinyl group. A compound having a (meth)acryloyl group is preferably used. Here, the (meth)acryloyl group refers to an acryloyl group and / or a methacryloyl group.
[0044] The thickness of the adhesive layer included in the phase difference member is 1.3 μm or less, preferably 1.1 μm or less, and more preferably 0.9 μm or less. With such a thickness, an optical laminate with extremely excellent smoothness can be obtained. Specifically, when forming the adhesive layer, the adhesive may undergo hardening shrinkage. This hardening shrinkage may greatly affect the smoothness of the obtained optical laminate. In the above display system, the image may be enlarged in the lens portion (for example, by a convex lens), and the smoothness of the optical laminate may greatly affect visibility. With a thin adhesive layer, the influence of hardening shrinkage can be reduced, and an optical laminate with excellent smoothness can be obtained. In addition, with such an optical laminate, remarkably excellent visibility can be realized in the above display system. For example, a clear image without distortion can be realized. On the other hand, the thickness of the adhesive layer included in the phase difference member is preferably 0.5 μm or more, for example, from the viewpoint of durability.
[0045] The first protective member typically includes a substrate. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm, and further preferably 15 μm to 40 μm. The surface smoothness of the substrate is preferably 0.7 arcmin or less, more preferably 0.6 arcmin or less, and further preferably 0.5 arcmin or less. The surface smoothness can be measured by focusing irradiated light on the surface of the object.
[0046] The substrate may be made of any suitable film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins. Here, (meth)acrylic refers to acrylic and / or methacrylic. In one embodiment, the substrate is preferably made of a (meth)acrylic resin. By using a (meth)acrylic resin, a substrate having excellent smoothness (for example, satisfying the above-mentioned surface smoothness) can be formed by extrusion molding. Then, a protective member having excellent smoothness can be obtained.
[0047] The first protective member is preferably composed of a laminated film having a substrate and a surface treatment layer formed on the substrate. The thickness of the laminated film is preferably 10 μm to 80 μm, more preferably 15 μm to 60 μm, and even more preferably 20 μm to 45 μm. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and even more preferably 2 μm to 5 μm.
[0048] The surface treatment layer typically includes a hard coat layer. The hard coat layer is typically formed by applying a hard coat layer-forming material to a substrate and curing the applied layer. The hard coat layer-forming material typically includes a curable compound as a layer-forming component. The curing mechanism of the curable compound may be, for example, a thermosetting type or a photocurable type. The curable compound may be, for example, a monomer, an oligomer, or a prepolymer. Preferably, a polyfunctional monomer or oligomer is used as the curable compound. The polyfunctional monomer or oligomer may be, for example, a monomer or oligomer having two or more (meth)acryloyl groups, a urethane (meth)acrylate or an oligomer of a urethane (meth)acrylate, an epoxy-based monomer or oligomer, or a silicone-based monomer or oligomer.
[0049] The thickness of the hard coat layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.
[0050] The surface treatment layer preferably includes a functional layer. The functional layer preferably functions as an antireflection layer. In a preferred embodiment, the surface treatment layer includes the hard coat layer and the antireflection layer in this order from the substrate side. The thickness of the functional layer is preferably 0.05 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.1 μm to 2 μm.
[0051] The first protective member having a surface treatment layer may be disposed so that the surface treatment layer is located on the front side. Specifically, the surface treatment layer may be located on the outermost surface of the first laminated portion. The surface treatment layer may have any appropriate function. For example, the surface treatment layer preferably has an anti-reflection function from the viewpoint of suppressing light loss at the interface with air and improving visibility. In one embodiment, the first protective member preferably has a maximum value of 5° regular reflectance spectrum in the wavelength range of 420 nm to 680 nm of 2.0% or less, more preferably 1.2% or less, even more preferably 1.0% or less, and particularly preferably 0.8% or less. Here, the 5° regular reflectance can be measured, for example, by attaching the measurement target to a black acrylic plate using an adhesive to prepare a measurement sample, and using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, product name "U-4100") as a measurement device, with the angle of incidence of light on the measurement sample being 5°.
[0052] The surface smoothness of the first protective member is preferably 0.5 arcmin or less, more preferably 0.4 arcmin or less. In reality, the surface smoothness of the first protective member is, for example, 0.1 arcmin or more. The laminate smoothness of the optical laminate 100 is preferably 0.7 arcmin or less, more preferably 0.6 arcmin or less, and even more preferably 0.5 arcmin or less. When the optical laminate satisfies such laminate smoothness, the generation of diffuse light can be suppressed and the image can be suppressed from becoming unclear. The laminate smoothness of the optical laminate 100 is, for example, 0.1 arcmin or more. The laminate smoothness can be obtained by irradiating the target with irradiation light and detecting the reflection and transmission of each member constituting the target (laminate).
[0053] The optical laminate 100 may have excellent durability. For example, the optical laminate 100 has a laminate smoothness of preferably 0.7 arcmin or less, more preferably 0.6 arcmin or less, and even more preferably 0.5 arcmin or less after being placed in a temperature environment of 80° C. for 500 hours. In addition, the optical laminate 100 has a laminate smoothness of preferably 0.7 arcmin or less, more preferably 0.6 arcmin or less, and even more preferably 0.5 arcmin or less after being placed in a temperature environment of −40° C. for 500 hours.
[0054] The optical laminate 100 can have high transmittance. For example, the optical laminate 100 has a luminosity-corrected single transmittance Y value of, for example, 90% or more, preferably 93% or more, more preferably 94% or more, and even more preferably 95% or more.
[0055] The second laminated section 200 includes the reflective polarizing member 14 and an adhesive layer (e.g., a pressure-sensitive adhesive layer) disposed between the reflective polarizing member 14 and the second lens section 24. The second laminated section 200 further includes an absorptive polarizing member 28 disposed between the reflective polarizing member 14 and the second lens section 24, for example, from the viewpoint of improving visibility. The absorptive polarizing member 28 is laminated in front of the reflective polarizing member 14 via an adhesive layer (e.g., a pressure-sensitive adhesive layer) 44. The reflection axis of the reflective polarizing member 14 and the absorption axis of the absorptive polarizing member 28 can be disposed approximately parallel to each other, and the transmission axis of the reflective polarizing member 14 and the transmission axis of the absorptive polarizing member 28 can be disposed approximately parallel to each other. By laminating the reflective polarizing member 14 and the absorptive polarizing member 28 via an adhesive layer, the reflective polarizing member 14 and the absorptive polarizing member 28 are fixed, and it is possible to prevent the axial arrangement of the reflection axis and the absorption axis (the transmission axis and the transmission axis) from being misaligned. In addition, it is possible to suppress the adverse effects of an air layer that may be formed between the reflective polarizing member 14 and the absorptive polarizing member 28.
[0056] The second laminated section 200 further includes a second protective member 32 disposed behind the reflective polarizing member 14. The second protective member 32 is laminated to the reflective polarizing member 14 via an adhesive layer (e.g., a pressure-sensitive adhesive layer) 43. The second protective member 32 may be located on the outermost surface of the second laminated section 200. The first protective member 31 and the second protective member 32 are disposed opposite to each other with a space therebetween. The second protective member may be a laminated film having a base material and a surface treatment layer, as with the first protective member. In this case, the surface treatment layer may be located on the outermost surface of the second laminated section. The details of the second protective member may be the same as those of the first protective member. Specifically, the reflection characteristics, effects, smoothness, thickness, and constituent materials of the second protective member may be the same as those of the first protective member.
[0057] In the example shown in FIG. 2, the second laminated section 200 further includes a third phase difference member 30 disposed between the absorptive polarizing member 28 and the second lens section 24. The third phase difference member 30 is laminated to the absorptive polarizing member 28 via an adhesive layer (e.g., a pressure-sensitive adhesive layer) 45. The third phase difference member 30 is laminated to the second lens section 24 via an adhesive layer (e.g., a pressure-sensitive adhesive layer) 46, and the second laminated section 200 is provided integrally with the second lens section 24. The third phase difference member 30 includes, for example, a third λ / 4 member. The angle between the absorption axis of the absorptive polarizing member 28 and the slow axis of the third λ / 4 member included in the third phase difference member 30 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. By providing such a member, for example, reflection of external light from the second lens section 16 side can be prevented. When the third phase difference member does not include any member other than the third λ / 4 member, the third phase difference member may correspond to the third λ / 4 member.
[0058] The reflective polarizing element transmits polarized light (typically, linearly polarized light) parallel to its transmission axis while maintaining its polarization state, and can reflect light in other polarization states. The reflective polarizing element is typically composed of a film having a multilayer structure (sometimes referred to as a reflective polarizing film). In this case, the thickness of the reflective polarizing element is, for example, 10 μm to 150 μm, preferably 20 μm to 100 μm, and more preferably 30 μm to 60 μm.
[0059] FIG. 3 is a schematic perspective view showing an example of a multilayer structure included in a reflective polarizing film. The multilayer structure 14a has a layer A having birefringence and a layer B having substantially no birefringence alternately. The total number of layers constituting the multilayer structure may be 50 to 1000. For example, the refractive index nx in the x-axis direction of the A layer is larger than the refractive index ny in the y-axis direction, the refractive index nx in the x-axis direction of the B layer is substantially the same as the refractive index ny in the y-axis direction, and the refractive index difference between the A layer and the B layer is large in the x-axis direction and substantially zero in the y-axis direction. As a result, the x-axis direction can be the reflection axis, and the y-axis direction can be the transmission axis. The refractive index difference between the A layer and the B layer in the x-axis direction is preferably 0.2 to 0.3.
[0060] The A layer is typically made of a material that develops birefringence through stretching. Examples of such materials include naphthalene dicarboxylic acid polyesters (e.g., polyethylene naphthalate), polycarbonates, and acrylic resins (e.g., polymethyl methacrylate). The B layer is typically made of a material that does not substantially develop birefringence even when stretched. Examples of such materials include copolyesters of naphthalene dicarboxylic acid and terephthalic acid. The multilayer structure can be formed by combining coextrusion and stretching. For example, the material constituting the A layer and the material constituting the B layer are extruded, and then multilayered (e.g., using a multiplier). The resulting multilayer laminate is then stretched. The x-axis direction in the illustrated example can correspond to the stretching direction.
[0061] Commercially available reflective polarizing films include, for example, products manufactured by 3M under the trade names "DBEF" and "APF" and products manufactured by Nitto Denko Corporation under the trade name "APCF."
[0062] The crossed transmittance (Tc) of the reflective polarizing member (reflective polarizing film) may be, for example, 0.01% to 3%. The single transmittance (Ts) of the reflective polarizing member (reflective polarizing film) may be, for example, 43% to 49%, and preferably 45% to 47%. The degree of polarization (P) of the reflective polarizing member (reflective polarizing film) may be, for example, 92% to 99.99%.
[0063] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0064] The absorptive polarizing member may typically include a resin film (sometimes referred to as an absorptive polarizing film) containing a dichroic material. The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.
[0065] The absorptive polarizing film may be prepared from a single layer of resin film, or may be prepared using a laminate of two or more layers.
[0066] When preparing from a single-layer resin film, for example, an absorptive polarizing film can be obtained by subjecting a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, a stretching treatment, etc. Among them, an absorptive polarizing film obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferable.
[0067] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.
[0068] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the absorptive polarizing film), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / absorptive polarizing film laminate after peeling the resin substrate from the laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such an absorptive polarizing film are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0069] The crossed transmittance (Tc) of the absorptive polarizing member (absorptive polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the absorptive polarizing member (absorptive polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing member (absorptive polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.
[0070] The in-plane retardation Re(550) of the third λ / 4 member is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The third λ / 4 member preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The third λ / 4 member may have Re(450) / Re(550) of, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less. The third λ / 4 member preferably has a refractive index characteristic that satisfies the relationship nx>ny≧nz. The Nz coefficient of the third λ / 4 member is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0071] The third λ / 4 member is formed of any appropriate material that can satisfy the above characteristics. The third λ / 4 member can be, for example, a stretched resin film or an oriented and solidified layer of a liquid crystal compound. The same explanation as for the second λ / 4 member can be applied to the third λ / 4 member composed of a stretched resin film or an oriented and solidified layer of a liquid crystal compound. The second λ / 4 member and the third λ / 4 member may be members having the same configuration (e.g., forming material, thickness, optical properties, etc.) or may be members having different configurations.
[0072] The thickness of the adhesive layer used for laminating each of the above members can be set to any appropriate thickness. The thickness of each adhesive layer used for laminating each of the above members is preferably 3 μm or more and 20 μm or less, and may be 15 μm or less, 12 μm or less, or 7 μm or less. With such a thickness, the degree of unevenness on the surface of the adhesive layer can be suppressed, and the laminated portion can have excellent smoothness. EXAMPLES
[0073] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness, retardation value, and surface smoothness are values measured by the following measurement methods. Furthermore, unless otherwise specified, "parts" and "%" are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Phase difference value> The phase difference value at each wavelength at 23°C was measured using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"). <Surface smoothness> The surface smoothness was measured using a scanning white light interferometer (Zygo, product name "NewView9000"). Specifically, the measurement sample was placed on a measurement table with an anti-vibration table, interference fringes were generated using a single white LED light, and an interference objective lens (1.4x) with a reference surface was scanned in the Z direction (thickness direction) to selectively obtain the smoothness (surface smoothness) of the outermost surface of the measurement target within a 12.4mm square field of view. When the measurement object was an adhesive layer, the adhesive layer was attached to a microslide glass (manufactured by Matsunami Glass Industry Co., Ltd., product name "S200200"), and the smoothness of the exposed adhesive surface was measured. When the measurement object was a film, an acrylic adhesive layer with a thickness of 5 μm and minimal unevenness was formed on the glass, and the film to be measured was laminated onto this adhesive surface so as to prevent foreign matter, air bubbles, and deformation streaks from entering, and the smoothness of the surface opposite to the adhesive layer was measured. The surface smoothness of the acrylic adhesive layer with a thickness of 5 μm and minimal unevenness was 0.30 arcmin. For the analysis, the surface smoothness (unit: arcmin) was defined as double the angle index “Slope magnitude RMS” (equivalent to 2σ).
[0074] [Example 1] (Fabrication of λ / 4 components) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.
[0075] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 135μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a stretched film having a thickness of 47μm. The Re(550) of the obtained stretched film was 143nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.
[0076] (Positive C-plate formation) A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (1) (the numbers 65 and 35 in the formula indicate the mole percent of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a positive C plate with a thickness of 4 μm and an Rth(550) of -100 nm on the substrate. [ka]
[0077] (Creating protective materials) The hard coat layer forming material shown below was applied to an acrylic film (thickness 40 μm, surface smoothness 0.45 arcmin) having a lactone ring structure, heated at 90°C for 1 minute, and then irradiated the coating layer with a high-pressure mercury lamp with an integrated light intensity of 300 mJ / cm2. 2 The coating layer was cured by irradiation with ultraviolet light of 1000 .ANG. to prepare an acrylic film (thickness 44 .mu.m, surface smoothness on the hard coat layer side 0.4 arcmin) on which a hard coat layer of 4 .mu.m in thickness was formed. Next, the following coating solution A for forming an anti-reflection layer was applied onto the hard coat layer using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was then irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm2. 2 The coating was cured by irradiation with ultraviolet light of 1500 nm to form an antireflection layer A having a thickness of 140 nm. Next, the following coating solution B for forming an antireflection layer was applied onto the antireflection layer A using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 300 mJ / cm 2The coating was cured by irradiation with ultraviolet light of 1000 ohms to form an antireflection layer B having a thickness of 105 nm. In this way, a protective member (thickness: 44 μm, surface smoothness on the antireflection layer side: 0.4 arcmin) was obtained.
[0078] (Hard Coat Layer Forming Material) A hard coat layer forming material was prepared by mixing 50 parts of a urethane acrylic oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Oligo UA-53H"), 30 parts of a multifunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 20 parts of 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1 part of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100") and 3 parts of a photopolymerization initiator (manufactured by Ciba Japan, "Irgacure 907") and diluting with methyl isobutyl ketone to a solids concentration of 50%.
[0079] (Anti-reflection layer forming coating solution A) 100 parts by weight of a multifunctional acrylate (manufactured by Arakawa Chemical Industries, Ltd., product name "Opstar KZ6728", solid content 20% by weight), 3 parts by weight of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100"), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907", solid content 100% by weight) were mixed. The mixture was diluted with butyl acetate as a diluting solvent to a solid content of 12% by weight, and the mixture was stirred to prepare coating solution A for forming an anti-reflection layer.
[0080] (Anti-reflection layer forming coating solution B) 100 parts by weight of a polyfunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 150 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Surulia 5320", solid content 20% by weight, weight average particle diameter 75 nm), 50 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907", solid content 100% by weight) were mixed. To the mixture was added a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 as a dilution solvent until the total solids content was 4% by weight, and the mixture was stirred to prepare coating solution B for forming an anti-reflection layer.
[0081] (Preparation of adhesive) An adhesive was prepared by mixing 62 parts by weight of hydroxyethyl acrylamide (manufactured by Kojin Co., Ltd., trade name "HEAA"), 25 parts by weight of acryloyl morpholine (manufactured by Kojin Co., Ltd., trade name "ACMO"), 7 parts by weight of PEG400# diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Light Acrylate 9EG-A"), 3 parts by weight of BASF Co., Ltd., trade name "Irgacure 907", and 3 parts by weight of Nippon Kayaku Co., Ltd., trade name "KAYACURE DETX-S" for 60 minutes.
[0082] (Preparation of optical laminate) The adhesive was applied to the λ / 4 member (stretched film) so that the thickness after curing would be 0.6 μm, and the positive C plate was attached to obtain a retardation member. The above protective member (acrylic film with hard coat layer and antireflection layer formed thereon) was attached to the λ / 4 member side of the obtained retardation member via an adhesive layer having a thickness of 12 μm and a surface smoothness of 0.25 arcmin. Here, the acrylic film of the protective member was attached to the λ / 4 member side. Next, a pressure-sensitive adhesive layer having a thickness of 12 μm and a surface smoothness of 0.25 arcmin was formed on the positive C plate side of the retardation member to obtain an optical laminate.
[0083] [Example 2] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive was applied to the λ / 4 member so that the thickness after curing was 0.9 μm, and a positive C plate was attached to the adhesive.
[0084] [Example 3] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive was applied to the λ / 4 member so that the thickness after curing would be 1.3 μm, and a positive C plate was attached to it.
[0085] [Comparative Example 1] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive was applied to the λ / 4 member so that the thickness after curing would be 1.5 μm, and a positive C plate was attached to it.
[0086] [Comparative Example 2] An optical laminate was obtained in the same manner as in Example 1, except that the adhesive was applied to the λ / 4 member so that the thickness after curing was 1.9 μm, and a positive C plate was attached to the adhesive.
[0087] [Comparative Example 3] An optical laminate was obtained in the same manner as in Example 1, except that a pressure sensitive adhesive (thickness: 5 μm) was used instead of an adhesive when bonding the positive C plate to the λ / 4 member.
[0088] The optical laminates obtained in the examples and comparative examples were evaluated as follows. The evaluation results are shown in Table 1. (1) Smoothness of laminate The smoothness of the laminate was measured using a phase-shifting laser interferometer (manufactured by Zygo, product name "DynaFiz"). Specifically, the optical laminate was laminated onto a microslide glass (manufactured by Matsunami Glass Industry, product name "S200200") so as to prevent the inclusion of foreign matter, air bubbles, or deformation streaks. Next, degassing was performed using a pressurized degassing device (autoclave) to remove the effects of minute air bubbles. The degassing conditions were 50°C, 0.5 MPa, and 30 minutes. After degassing, the sample was allowed to cool at room temperature for 30 minutes or more to obtain a measurement sample. The sample was placed on a vibration-proof measuring table, and a single-wavelength (633 nm) laser was used to interfere with a standard with guaranteed flatness, and the relative displacement within a specified area (a circle of 30 mm diameter) was measured. For the analysis, the angle index "Slope magnitude RMS" obtained by extracting the frequency values from 0.1 / mm to 1 / mm was doubled (equivalent to 2σ) and defined as the laminate smoothness (unit: arcmin). (2) Appearance The appearance of the optical laminate (light transmitted through the lens) was evaluated using an optical lens (manufactured by Thorabs, product name "LA1145") and a point light source (manufactured by Hamamatsu Photonics, model number "L8425-01"). Specifically, the optical laminate cut into a circular shape of 45 mmφ was laminated on the flat side of the optical lens so that no foreign matter, air bubbles, or deformation lines would get into the surface. Next, in order to remove the effects of minute air bubbles, degassing was performed using a pressurized degassing device (autoclave). The degassing conditions were 50°C, 0.5 MPa, and 30 minutes. After degassing, the sample was left to cool at room temperature for 30 minutes or more to obtain a measurement sample. A point light source, an optical lens (measurement sample), and a screen were placed in this order, and the light from the point light source through the optical lens was projected onto the screen to evaluate its appearance. Here, the lens was held by a holder at a position where the light from the point light source was incident on the convex side of the optical lens. The distance from the point light source to the screen was 1050 mm, and the distance from the optical lens to the screen was 130 mm. The appearance was evaluated by 10 evaluators who visually observed the light projected through an optical lens on a screen and judged the presence or absence of wrinkles or waviness. The number of evaluators who judged there to be no wrinkles or waviness is shown in Table 1. (3)Durability A thermal shock test was performed on the optical laminate using a thermal shock device (manufactured by Espec Corporation, product name "TSA-303EL-W"). The optical laminate cut into a 45 mmφ circle using a laser processing machine was attached to a glass plate, and then placed in a temperature environment of -40°C for 0.5 hours, and then placed in a temperature environment of 85°C for 0.5 hours. The time required for heating and cooling was set to within 6 minutes. After repeating this operation a total of 100 times, the appearance of the optical laminate was visually observed to check for the presence or absence of cracks and peeling. (Evaluation Criteria) Good: No cracks or peeling observed Poor: Cracks and / or peeling are observed. (4) Transmittance The optical laminate was measured for single transmittance Ts using an ultraviolet-visible spectrophotometer (V-7100, manufactured by JASCO Corporation). Ts is a Y value measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. The optical laminate was measured without being attached to a substrate such as glass.
[0089] [Table 1]
[0090] In the durability evaluation, cracks were confirmed in the positive C plate, which was thinner than the λ / 4 member, in Comparative Example 3. The cracks were 10 mm or longer, multiple cracks were generated from the end of the sample, and were visible to the naked eye. On the other hand, the optical laminate of Example 1 was placed in a temperature environment of 80°C for 500 hours or in a temperature environment of -40°C for 500 hours, and then subjected to the various evaluations described above. The results obtained were similar to those obtained when no such temperature treatment was performed (results shown in Table 1).
[0091] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same action and effect, or a configuration that can achieve the same purpose. [Industrial Applicability]
[0092] The optical laminate according to the embodiment of the present invention can be used for a display such as VR goggles. [Explanation of symbols]
[0093] 2 display system, 4 lens portion, 12 display element, 14 reflective polarizing member, 16 first lens portion, 18 half mirror, 20 first phase difference member, 22 second phase difference member, 24 second lens portion, 28 absorptive polarizing member, 30 third phase difference member, 31 first protective member, 32 second protective member, 41 adhesive layer, 42 adhesive layer, 43 adhesive layer, 44 adhesive layer, 45 adhesive layer, 46 adhesive layer, 50 adhesive layer, 100 first laminate portion (optical laminate), 200 second laminate portion.
Claims
1. An optical member set including an optical laminate including a polarizing member, a first λ / 4 member, and a second λ / 4 member, and a reflective polarizing member, The respective members included in the optical member set are arranged such that light emitted forward from a display element passes through the polarizing member, the first λ / 4 member and the optical laminate in this order, is reflected by the reflective polarizing member, passes through the optical laminate, is reflected forward, and passes through the optical laminate and the reflective polarizing member in this order; The optical laminate includes a laminate film having a substrate and a surface treatment layer, and a retardation member, The substrate of the laminated film and the phase difference member are disposed adjacent to each other, the retardation member includes a first retardation layer, an adhesive layer, and a second retardation layer in this order; The adhesive layer is a cured layer of a resin, The thickness of the adhesive layer is 0.5 μm or more and 1.3 μm or less, The first retardation layer corresponds to the second λ / 4 member. Optical component set.
2. The optical member set according to claim 1 , wherein the optical laminate has a laminate smoothness of 0.7 arcmin or less.
3. The optical member set according to claim 1 , wherein the surface smoothness of the laminated film is 0.5 arcmin or less.
4. The optical member set according to claim 1 , wherein the base material of the laminated film contains a (meth)acrylic resin.
5. The optical member set according to claim 1 , wherein the surface treatment layer of the laminated film has an anti-reflection function.
6. The optical member set according to claim 1, wherein the first retardation layer exhibits a refractive index characteristic of nx>ny≧nz and satisfies a relationship of Re(450)<Re(550)<Re(650). Here, Re(450) indicates an in-plane retardation measured with light having a wavelength of 450 nm at 23° C., Re(550) indicates an in-plane retardation measured with light having a wavelength of 550 nm at 23° C., and Re(650) indicates an in-plane retardation measured with light having a wavelength of 650 nm at 23° C.
7. The optical member set according to claim 1 , wherein the second retardation layer exhibits a refractive index characteristic of nz>nx≧ny.
8. The optical member set according to claim 1 , wherein the Y value of the visibility-corrected single transmittance of the optical laminate is 93% or more.
Citation Information
Patent Citations
Brightness improving film, method of manufacturing the same, optical film and image display device
JP2003337221A
Optical element, composite optical element using the same, and method for manufacturing them
JP2005049652A
Optical film and its manufacturing method, and polarizing plate and display device
JP2005134713A
Compact collimator for polarized light with high contrast
JP2022540833A
Improved adhesive for PC-MOF application
US20210221079A1